Троянський кінь грецьких майстрів - Полідович, Ю.Б. (Археологія і давня історія України, 2022)
У статті детально аналізуються зображення на золотих оббивках горитів чортомлицького типу. Деталізується і уточнюється трактування сцен із життя Ахілла. Робиться припущенні щодо магічної складової зображень, сюжет яких майстром був ретельно відібраний і продуманий. The paper analyzes the images on the gold gorytos covers of the second half of the 4th century BC (fig. 1). These items were found in the Chertomlyk kurgan (now the Dnipropetrovsk Oblast, Ukraine), the Melitopol kurgan (now the Zaporizhia Oblast, Ukraine), the kurgan near the town of Ilyintssi (now Vinnytsia Oblast, Ukraine) and the kurgan 8 from group of Piat’ bratiev (Five Brothers) near the stanitsa Elizavetinskaya (now the Rostov Oblast, Russia). All gorytos covers are of the same size. They were made using a bronze matrix (or a set of matrices) at the same time and in the same workshop. Most modern researchers accept the interpretation of the central images on the gorytos covers as the scenes from the life of Achilles, the hero of the Greek epic, who was revered by Greeks as divine protector. K. Robert proposed this interpretation in 1891. B. V. Farmakovsky singled out five scenes from the life of Achilles which sequentially represent the Hero from his childhood to the death (fig. 2: 1). In this paper the author identifies nine scenes (fig. 2: 2). Upper frieze: 1) a young man (possibly Apollo) teaches the boy Achilles archery; Thetis stands side by side, she worries about the fate of her son Achilles (fig. 3: 3); 2) Achilles says his mother Thetis goodbye before leaving to the island of Skyros; 3) Odysseus finds Achilles on the island of Skyros; 4) Deidamia, the wife of Achilles, runs away in despair; 5) Peleus hands over his weapon to his son Achilles. Lower frieze: 6) Briseis regrets her fate as a slave (fig. 3: 1—2); 7) Zeus establishes the events in the fates of the heroes (fig. 3: 4); 8) Achilles accepts the gifts from Agamemnon and makes peace with him, a wounded Odysseus is standing beside him; 9) Thetis carries the bag with ashes of Achilles and mourns his death (fig. 3: 5). All scenes tell about the events that preceded the manifestation of Achilles as a great warrior and hero: the beginning of warfare training, the events on the eve of the beginning of the Trojan War, the events at the walls of Troy and the quarrel with Agamemnon. Perhaps these images are associated with the magic of knowledge about the beginning, about the origin. In this case, this is knowledge about the origin of Achilles as a hero. Such magical knowledge made it possible to wield the power of the Protector Hero and direct it to the right direction like a prayer or a spell. Gorytos was the Scythian weapon. This gorytos series was made in some workshop of a Greek city-state, possibly in the Bosporus kingdom. They were donated to the Scythian rulers with a secret purpose: with the help of magical images to restrain the warlike moods of the Scythians, to pacify them. Therefore, these gorytos were like a wooden horse which, according to the Greek epic, the Achaean warriors left as the so-called gift of Troy and with its help captured this impregnable city.